HUBUNGAN PELAKSANAAN DISCHARGE PLANNING DENGAN TINGKAT KEPUASAN PASIEN DI RUANG SERUNI RSUD TAMAN HUSADA BONTANG - Nani Subiyanti; , Hilda Hilda; Wiyadi Wiyadi (Bajang Institute, 2024)
Background: Hospitals are places that provide health services to the community. The quality of health services greatly influences the sustainability and progress of hospital health services. Patient satisfaction is a comparison between the quality of services obtained and the patient's desires, needs and expectations. One of the health services in question is discharge planning. Failure to fulfill discharge planning services will result in information not reaching patients and their families, and can lead to disease recurrence or readmissions, resulting in patients feeling dissatisfied with hospital services. The aim of this study was to analyze the relationship between the implementation of discharge planning and the level of patient satisfaction in the Seruni Room at Taman Husada Bontang Regional Hospital Method: The method used in this research is analytical observational with a cross sectional approach. Respondents were 50 people with the inclusion criteria of cooperative patients aged 18-50 years, using total sampling technique. The instrument uses a discharge planning implementation questionnaire with a Likert scale of 17 question items and a satisfaction level questionnaire of 15 question items. Results: The research showed that the majority of respondents stated that the implementation of discharge planning was in the good category, namely 56%. Most respondents were satisfied with the implementation of discharge planning, namely 74%. Statistical test results using Spearman's rho value sig(2-tailed) = 0.000 and a correlation coefficient value of 0.748. This means that there is a significant and unidirectional relationship between the implementation of discharge planning and the level of patient satisfaction with sufficient correlation strength. Conclusion: there is a relationship between the implementation of discharge planning and the level of patient satisfaction. If the implementation of discharge planning is improved, the level of patient satisfaction will increase